Anxiety disorders therapy in general practice - L. A. Ivanova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Anxiety disorders among general practice patients are the most common. We examined the efficacy and safety of Buspirone in patients with anxiety disorders in outpatient practice. In accordance with lCD-10, the patients were distributed as follows: generalized anxiety disorder - 38.7 %, panic disorder - 29 %, adjustment disorder in the form of mixed depressive and anxiety reaction - 32.3 %. In order to evaluate the impact of therapy the following research methods were used: clinical, clinical-psychopathological, psychometric (Hamilton anxiety scale (HaM-А), Spielberger-Hanin anxiety level self-evaluation scale, Shihan anxiety self-evaluation scale, Clinical Global lmpression-Severity Scale (CGl-S), and Clinical Global Impression of Improvement (CGl-l) Scale. Among patients with anxiety disorders 28 people (90.3 %) have finished the study, three persons (9.7 %) dropped out of the study with regard to the ineffectiveness of Buspirone therapy. Analysis of the values on the HAM-А scale revealed statistically significant reduction in composite score by the end of day 14 (by 23.4 %, p < 0.05) and a statistically significant increase in differences by day 35 of therapy and reduction of scores by 51.5 % (p < 0.01). A statistically significant reduction (by 21.9 %, p < 0.05) of points on the Shihan anxiety scale was revealed by day 21 of therapy. Reduction of the mean values of the total score of reactive and personal anxiety by the Spielberger - Hanin scale was recorded from day 21 of therapy (p < 0.05). CGl-S scale statistically reliable reduction of patients with moderate degree of severity to 26.6 % (p < 0.05) and a statistically significant increase in the number of patients with mild degrees of severity by 20 % (p < 0.05) were revealed on day 14 of therapy. On the CGl-l scale, a marked improvement (26.7 %, p < 0.05) and a slight improvement (33.3 %, p < 0.05) is achieved by day 14 of therapy. Undesirable effects in the form of motor coordination disturbance, drowsiness, dizziness leveled during the therapy and did not require additional prescriptions for their correction. Buspirone can be recommended as an effective anxiolytic drug with safe portability profile for the treatment of anxiety disorders.